Roadmap for Long-Term Macroplastic Monitoring in Rivers - van Emmerik, Tim; Vriend, Paul; Copius Peereboom, Eric (Frontiers in Environmental Science, 2022)
Macroplastic pollution in and around rivers negatively impacts human livelihood, and aquatic ecosystems. Monitoring data are crucial for better understanding and quantifying this problem, and for the design of effective intervention strategies. However, current monitoring efforts are often of short duration, or study single river compartments. We present a “Roadmap” to overcome the challenges related to the design and implementation of long-term riverine macroplastic monitoring strategies. This “Roadmap” can help accelerating the process of achieving structural monitoring through providing a stepwise approach, which links monitoring goals and research questions to the data and methods required to answer them. We identify four monitoring goals: 1) policy, 2) knowledge development, 3) operations, and 4) solutions. Linked to these, we provide a non-exhaustive list of 12 globally common research questions that are important to answer to reach these goals. The “Roadmap” takes these questions and links them to development levels of monitoring methods for each river compartment: 1) method development, 2) baseline assessment, and 3) long-term monitoring. At each level, specific questions can only be answered if the level is achieved for specific river compartments. For questions at higher levels, the previous levels need to be achieved first. This creates a clear stepwise approach to solve open challenges. With the “Roadmap”, we provide a new tool to support decision-making and planning of specific projects by policy makers. The “Roadmap” is a clear and stepwise, yet flexible framework that allows to add and remove elements based on new insights, available resources, and other relevant changes.